Dosimetric Effects of the Interfraction Variations during Whole Breast Radiotherapy: A Prospective Study - Jacob, Julian; Heymann, Steve; Borget, Isabelle; Dumas, Isabelle; Riahi, Elyes; Maroun, Pierre; Ezra, Patrick; Roberti, Elena; Rivera, Sofia; Deutsch, Eric; Bourgier, Céline (Frontiers in Oncology, 2015)
Introduction: The aim of this work was to assess the dosimetric impact of the interfraction variations during breast radiotherapy. Material and methods: Daily portal imaging measurements were prospectively performed in 10 patients treated with adjuvant whole breast irradiation (50 Gy/25 fractions). Margins between the Clinical Target Volume (CTV) and the Planning Target Volume (PTV) were 5 mm in the three dimensions. Parameters of interest were the Central Lung Distance (CLD) and the Inferior Central Margin (ICM). Daily movements were applied to the baseline treatment planning (TP1) to design a further TP (TP2). The PTV coverage and organ at risk exposure were measured on both TP1 and TP2, before being compared. Results: A total of 241 portal images were analyzed. The random and systematic errors were 2.6 mm and 3.7 mm for the CLD, 4.3 mm and 6.9 mm for the ICM, respectively. No significant consequence on the PTV treatments was observed (mean variations: +0.1%, p=0.56, and -1.8%, p=0.08 for the breast and the tumor bed, respectively). The ipsilateral lung and heart exposure was not significantly modified. Conclusion: In our series, the daily interfraction variations had no significant effect on the PTV coverage or healthy tissue exposure during breast radiotherapy.